The Endoplasmic Reticulum Chaperone GRP78/BiP Modulates Prion Propagation in vitro and in vivo - Park, Kyung-Won; Eun Kim, Gyoung; Morales, Rodrigo; Moda, Fabio; Moreno-González, Inés; Concha-Marambio, Luis; Lee, Amy S.; Hetz, Claudio; Soto, Claudio (Springer Nature, 2017)
Prion diseases are fatal neurodegenerative disorders affecting several mammalian species, characterized by the accumulation of the misfolded form of the prion protein, which is followed by the induction of endoplasmic reticulum (ER) stress and the activation of the unfolded protein response (UPR). GRP78, also called BiP, is a master regulator of the UPR, reducing ER stress levels and apoptosis due to an enhancement of the cellular folding capacity. Here, we studied the role of GRP78 in prion diseases using several in vivo and in vitro approaches. Our results show that a reduction in the expression of this molecular chaperone accelerates prion pathogenesis in vivo. In addition, we observed that prion replication in cell culture was inversely related to the levels of expression of GRP78 and that both proteins interact in the cellular context. Finally, incubation of PrPSc with recombinant GRP78 led to the dose-dependent reduction of protease-resistant PrPSc in vitro. Our results uncover a novel role of GRP78 in reducing prion pathogenesis, suggesting that modulating its levels/activity may offer a novel opportunity for designing therapeutic approaches for these diseases. These findings may also have implications for other diseases involving the accumulation of misfolded proteins.
Keywords: Priones; Prion